The UK: investigating who we are - Scoffham, Stephen; Whyte, Terry (Geography plus: primary teachers' toolkit, 2011)
The UK allows pupils in years 4–6 (ages 8 to 11) to explore in eight lessons with starter, main and plenary activities, what it is like to live in the UK in the first part of the 21st century. Pupils start by developing their locational knowledge of the UK with maps, atlases and photographs before proceeding to consider issues of identity and the UK’s changing population. These lessons provide varied starting points, which will help to equip pupils with a better understanding of the contemporary world, and their role as citizens.